Biofuel Production from Cellulosic Wastes by Local Isolates of Streptomyces sp. - H. Hayder, Nadem; Mahmoode , Banan (Iraqi Journal of Science, 2025)
The current study aims to produce cellulase enzyme from Streptomyces spp. isolates and study the effect of some cultural conditions on cellulase production; biofuel production from cellulotic waste through enzymatic and acids hydrolysis. Out of 74 isolates of Streptomyces sp. were screened for cellulse production in solid and liquid media. Results showed higher capability of isolate Streptomyces sp. B 167 for cellulase production and bioconversion of cellulose, therefore selected for further studies. The results of optimization revealed that the cellulase enzyme productivity by the selected isolate reached 2.1 and 2.28 U/ml after 48 h of incubation time and pH 7 respectively. Cellulase productions in tested isolate improved (2.57 U/ml) by supplementation of cellulose liquid medium with 1 % of yeast extract as nitrogen source. Additives of carbon sources like (manitol, glucose, maltose, sucrose and starch) to the process of saccharification not improve the cellulose productivity. The bioconversion of cellulosic waste to reducing sugar was maximum with Banana peels (77.78 %) followed by the rice husk (75.56 %), orange peels (71.11 %), corn steep peels (60.0 %) and lowest bioconversions (53.33 %) recorded with sawdust. The degradation of cellulosic waste increases with increasing substrate concentration. Maximum cellulase productivity (3.18 U/ml) and bioconversion (86.1 %) was obtained at 3 % (w/v) of cellulosic waste (Banana peels). Saccharification of cellulosic waste with different treatment methods was studied. The pretreatment of cellulosic waste with 1 % HCl and H2SO4 produces 21 and 15.8 g of reducing sugar / 100 g of cellulosic waste. In comparison, hydrolysis with Streptomyces sp. B 167 enzymes, resulting significantly higher amount of reducing sugar yield (25 g / 100 g cellulotic waste). Further fermentation of cellulosic hydrolysates were preformed using Saccharomyces cerevisiae using stationary fermentation condition, maximum yield of ethanol were ( 0.30, 0.19 and 0.10 g ethanol / g glucose) observed with Streptomyces sp. B 167 enzymes, HCl and H2SO4 hydrolysates respectively after 48 h of fermentation.